RETRACTED: Energy efficiency assessment of alternative power supply system for isothermal wagon for live fish transportation - Balalaev A.N.; Korkina S.V.; Plokhov E.M. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001